ARE THE FINANCIAL SERVICES’ CUSTOMERS TRULY LOYAL? AN INVESTIGATION IN THE PORTUGUESE PRIVATE BANKING SECTOR - José de Sousa Martins; Arnaldo Fernandes Matos Coelho (Revista Gestão em Análise, 2016)
This study aims at understanding how loyalty is formed and which variables contribute the most to build strong and stable relationships with customers. This research is based on a sample of 403 customers of private banks in Northern Portugal. Data collection was made using structured questionnaire, applied directly to these customers. A Multiple Linear Regression modelling approach was adopted to assess the proposed hypothesis. The results of this investigation show that the relationships between customers and their main banks seem to be based on a more transactional logic. It is based on the perceived value and the switching costs, and satisfaction remains as the main driver. Nevertheless, there seems to be room for further exploitation of the psychological variables such as emotions, once they have shown an important role on satisfaction.